A companion to the Reformation in Geneva - Balserak, Jon (Brill's companions to the Christian tradition, 2021)
"A Companion to the Reformation in Geneva describes the course of the Protestant Reformation in the city of Geneva from the 16th to the 18th centuries. It seeks to explore the beginnings of reform in the city, the struggles the reformers encountered when seeking to teach, minister to, educate, and discipline the inhabitants of Geneva, and the methods employed to overcome these obstacles. It examines Geneva's relations with nearby cities and how Geneva handled the influx of immigrants from France"--